2022
DOI: 10.1021/acs.jpca.2c01063
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Cooling Effect on the Rate Constant in the CH3F + Ca+ Reaction at Low Collision Energies

Abstract: The rotational cooling effect on the reaction rate constant of the gas-phase ion–polar-molecule reaction CH3F + Ca+ → CH3 + CaF+ was experimentally studied at low collision energies. Fluoromethane molecules showed higher reactivity as the rotational temperature decreased. The experimental rate constants were compared with the capture rate constants which were obtained by the Perturbed Rotational State (PRS) theory assuming the rotational level distribution corresponding to the experimental conditions. The PRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…However, this is hardly the only novel result. In this virtual special issue, N 2 O is reacted with C­( 3 P), producing rate coefficients for such chemical processes, and a similar study on fluoromethane and calcium atomic cations is also reported . Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, NO + the propargyl radical generates branching ratios for eight common astrochemical products, furan + H 2 reactions generate various c -C 4 H x O ( x = 4–8) species, myriad nitrous oxides are synthesized in H 2 O–N 2 O/N 2 ice mixtures, , dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, and porous amorphous solid water appears to catalyze interstellar organic chemistry .…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, this is hardly the only novel result. In this virtual special issue, N 2 O is reacted with C­( 3 P), producing rate coefficients for such chemical processes, and a similar study on fluoromethane and calcium atomic cations is also reported . Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, NO + the propargyl radical generates branching ratios for eight common astrochemical products, furan + H 2 reactions generate various c -C 4 H x O ( x = 4–8) species, myriad nitrous oxides are synthesized in H 2 O–N 2 O/N 2 ice mixtures, , dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, and porous amorphous solid water appears to catalyze interstellar organic chemistry .…”
mentioning
confidence: 84%
“…In this virtual special issue, N 2 O is reacted with C( 3 P), producing rate coefficients for such chemical processes, 21 and a similar study on fluoromethane and calcium atomic cations is also reported. 22 Additionally, the deuterated ethynyl radical is reacted with propylene producing a wealth of hydrocarbons, 23 NO + the propargyl radical generates branching ratios for eight common astrochemical products, 24 furan + H 2 reactions generate various c-C 4 H x O (x = 4−8) species, 25 myriad nitrous oxides are synthesized in H 2 O−N 2 O/N 2 ice mixtures, 26,27 dinitriles are shown to be produced from gas-phase reactions of cyano radicals and cyanoethane, 28 and porous amorphous solid water appears to catalyze interstellar organic chemistry. 29 From theory, the earliest molecule in the universe (HeH + ) is most efficiently rotationally excited by collisions with H 2 , 30 H 2 CCS and HCCSH are likely not detected since they are destroyed through barrierless reactions with atomic hydrogen, 31 and MgNC reacts with water clusters to produce the known HMgNC molecule along with other Mg-containing species.…”
mentioning
confidence: 99%
“…The use of trapping and laser cooling methods to produce ensembles of translationally cold ions is an area of active research interest. Much of this interest is inspired by the diverse range of applications for cold, confined ionsincluding their use as qubits, , in the determination of fundamental constants, , for precision measurements, and for the study of chemical reaction dynamics and kinetics. As many ionic species of interest cannot be easily or efficiently laser-cooled, Coulomb crystals have emerged as a useful tool for the study of processes involving sympathetically cooled trapped ions.…”
Section: Introductionmentioning
confidence: 99%